Uso da ropivacaína ou levobupivacaína na anestesia epidural toraco-lombar em cães - Jacobina, Guilherme Costa (2009)
Based on current progress of the anesthetic techniques, it is necessary to experiment with new local anesthetics. Ropivacaine and levobupivacaine are recent formulations of long duration, the amide group, which have lower toxicity that bupivacaine. The thoracic epidural anesthesia is still little explored in Veterinary Medicine today. The purpose of this study was to compare these two local anesthetics in the lumbar-thoracic epidural anesthesia. Study standardized, blind, was performed in 16 dogs, subjected to epidural anesthesia through epidural catheter placed near the T13-L1, into two groups (n = 8), treated with ropivacaine 0.5% (GR) or levobupivacaine 0.5%(GL) both at dose 2mg/kg. We evaluated the heart rate (HR) and respiratory (f), mean arterial pressure (MAP), systolic (SAP), diastolic (DAP), motor and sensory latency period, duration of sensory and motor block, cranial and caudal extension of the blockade, as well as assess side effects. Both groups had similar clinical profiles inside from the standards physiology except by reduction on arterial pressure. The GL showed higher motor block (477.5±65.2) minutes compared to GR (271.3±97.17) minutos. Both treatments promoted excellent analgesia dermatomes evaluated in all regions of thoracic and lumbar.